Marketing Strategy Analysis Using Apriori Association Method To Increase Sales In E-Commerce Companies - Okviannas, Nadilla; Widianto, Sunu; Komaladewi, Rita (Dinasti Publisher, 2025)
This research aims to analyze marketing strategies by utilizing association data mining algorithms, specifically Apriori and FP-Growth, to increase sales in e-commerce companies. The data used consists of actual sales data from Blibli.com, analyzed using RapidMiner to identify significant purchasing patterns. The analysis results show a strong association between products such as